Girl in pieces - Glasgow, Kathleen, 1969- (2020)
"Charlotte Davis is in pieces. At seventeen she's already lost more than most people lose in a lifetime. But she's learned how to forget. The broken glass washes away the sorrow until there is nothing but calm. You don't have to think about your father and the river. Your best friend, who is gone forever. Or your mother, who has nothing left to give you. Every new scar hardens Charlie's heart just a little more, yet it still hurts so much. It hurts enough to not care anymore, which is sometimes what has to happen before you can find your way back from the edge."--
"Originally published in hardcover in the United States by Delacorte Press, an imprint of Random House Children's Books, New York, in 2016"--Title page verso
Includes a discussion guide (pages [407]-420) and an excerpt of How to make friends with the dark.
Accelerated Reader AR
Keywords: Survival -- Juvenile fiction; Cutting (Self-mutilation) -- Juvenile fiction; Suicidal behavior -- Juvenile fiction; Absentee fathers -- Juvenile fiction; Abusive mothers -- Juvenile fiction; Abandoned children -- Juvenile fiction; Sex crimes -- Juvenile fiction; Homeless persons -- Juvenile fiction; Young adult fiction